Pengaruh Penerapan Model Pembelajaran Probing Prompting dan Contextual Teaching and Learning Terhadap Hasil Belajar Ditinjau dari Motivasi Belajar Siswa Sekolah Menengah Kejuruan - Putri Yulia; Sri Utami Ningsih (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2018)
The purpose of this research is to determine: (1) Differences of students learning result using Probing-Prompting models and Contextual Teaching and Learning (2) Differences in learning outcomes between students who have low motivation, moderate and high. (3) The interaction between the learning model (Probing-Prompting and Contextual Teaching and Learning) with student's learning motivation. This type of research is experimental research with factorial design 2x3. The population of this research is all students in ten classes of SMK Teladan Batam. Sampling was done by cluster random sampling technique, therefore the research sample is two classes, class X Teknik Kendaraan Ringan as an experimental class I and class X Teknik Konstruksi Kapal Baja as an experimental class II. The instrument of data collection applied was the value of midterm test II, a questionnaire about learning motivation, and the result of learning mathematics lessons test. The prerequisite test included the population normality test using the Lilliefors method and homogeneity test of population variance using the Bartlett method. The hypothesis testing was done using a two-way analysis of variance with a different cell. The result of the research showed that: (1) The Probing-Prompting models and Contextual Teaching and Learning the same learning outcomes. (2) The result of student learning which has a low learning motivation, medium, and high education outcomes are the same. (3) There is no interaction between the learning (Probing Prompting and Contextual Teaching and Learning) with the learning motivation.